Nanostructured poly(benzimidazole) membranes by N-alkylation - J. Weber; P. Haro Dominguez; K. Grygiel (eXPRESS Polymer Letters)
Modification of poly(benzimidazole) (PBI) by N-alkylation leads to polymers capable of undergoing microphase separation. Polymers with different amounts of C18 alkyl chains have been prepared. The polymers were analyzed by spectroscopy, thermal analysis, electron microscopy and X-ray scattering. The impact of the amount of alkyl chains on the observed microphase separation was analyzed. Membranes prepared from the polymers do show microphase separation, as evidenced by scattering experiments. While no clear morphology could be derived for the domains in the native state, evidence for the formation of lamellar morphologies upon doping with phosphoric acid is provided. Finally, the proton conductivity of alkyl-modified PBI is compared with that of pure PBI, showing that the introduction of alkyl side chains does not result in significant conductivity changes.